Stoning of St Paul and scourging of St Paul : designs by Abraham Van Diepenbeeck (1596-1675) for a series of stained glass windows in St Paul's Church in Antwerp - Manderyck, Madeleine (Phoebus focus, 2021)
In this edition of 'Phoebus Focus', no less than three specialists examine two of the sketches that Baroque master Abraham Van Diepenbeeck made for the stained-glass windows of the Antwerp St. Paul's Church. The stained-glass windows themselves have not survived the ravages of time and so these sketches are invaluable for the reconstruction of the church's original interior